Prevalence of Diabetes mellitus, Hypertension and Proteinuria in a Rural area of Bangladesh - Hasan, Mahmud Javed; Muqueet, Abdul; Sharmeen, Atia; Rahman, Masudar; Ahmed, Tofayel Uddin; Haque, Amdadul; Quddush, ASM Ruhul; Bari, Md Abdul (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13857 Community Based Medical Journal Vol.1(2) 2012 8-13